Inhaled Isopropyl Alcohol and Intravenous Ondansetron for Postoperative Nausea and Vomiting in Patients Undergoing Laparoscopic Surgery: A Cross-Sectional Study - Bohara, Chetan; Bhandari, Parshal; Giri, Kshitizma; Bimali, Aayush; Bajracharya, Prashanna (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Post-operative nausea and vomiting are frequently encountered complications in the post operative care unit. Effective treatment is promptly warranted to decrease morbidity of patients. Female gender, nonsmoker, young age, laparoscopic gastrointestinal surgeries are major risk factors. Ondansetron is commonly used for its prevention and treatment. However, inhaled isopropyl alcohol can also be used and has recently been in practice. In this study we compared inhaled isopropyl alcohol and intravenous ondansetron for the effective treatment of post operative nausea and vomiting after laparoscopic surgery among female patients. Methods: The present study conducted at Lumbini Medical College and Teaching Hospital included 76 female patients, aged between 18 to 60 years, classified as American Society of Anesthesiologist physical status classification I–II, who were scheduled for laparoscopic surgery. At the time of preoperative evaluation, patients were divided into two groups, i.e., Group I and Group O, each consisting of 38 patients. Post surgery, patients who experienced post operative nausea and vomiting in the recovery room either received inhalational treatment with 70% isopropyl alcohol (Group I) or 4mg intravenous ondansetron (Group O). Nausea levels were monitored using a verbal numeric rating scale (VNRS) at regular time intervals. The treatment was considered successful if the patient's nausea and vomiting score decreased by 50% or more. Results: Among 76 patients, 29(38.16%) developed post-operative nausea and vomiting. Both groups had similar baseline characteristics and initial post operative nausea and vomiting severity with p-value>0.05. Group I experienced faster symptom relief, achieving 50% reduction in symptoms in 4.69 ± 2.02 minutes compared to 7.73 ± 2.59 minutes in the Group O (p<0.05). Conclusions: Inhaled 70% isopropyl alcohol provided faster relief from postoperative nausea and vomiting when compared to intravenous ondansetron.